Does Shariah Supervisory Board Matter in Explaining Islamic Social Reporting by Indonesian Islamic Commercial Banks? - Rifdah Safinatun Najah; Dita Andraeny (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This study aimed to investigate the impact of Sharia Supervisory Board (SSB) on Islamic Social Responsibility (ISR) by Islamic Commercial Banks in Indonesia. Secondary data were collected from the annual reports of 14 Islamic Commercial Banks in Indonesia from 2010 to 2020, resulting in 125 firm-year data. A panel data regression was applied to analyze the data. The analysis results show that SSB age, cross-membership, and meeting frequency have a positive effect on ISR, whereas size has a negative effect. However, this analysis results did not manage to support the effect of SSB qualifications (Ph.D.) and expertise on ISR. The findings imply that SSB needs to increase the frequency of meetings to improve its supervisory function over Shariah banks' management, including in encouraging more comprehensive ISR disclosure. The contribution of this research is that research focuses on the characteristics of SSB on ISR by using Sharia Enterprise Theory (SET) to provide a better understanding of how these factors influence the implementation of ISR in the sharia context. Keywords: Sharia Supervisory Board Characteristics, Social Reporting, Islamic Bank, Indonesia ABSTRAK Tujuan dari penelitian ini adalah untuk menyelidiki dampak SSB terhadap Islamic Social Reporting (ISR) oleh Bank Umum Syariah di Indonesia. Data sekunder dikumpulkan dari laporan tahunan 14 Bank Umum Syariah di Indonesia sejak 2010 hingga 2020, menghasilkan 125 data firm-year. Regresi data panel diterapkan untuk menganalisis data. Hasil analisis menunjukkan bahwa usia SSB, lintas keanggotaan, dan frekuensi pertemuan berpengaruh positif pada ISR, sedangkan ukuran berpengaruh negatif. Namun hasil analisis ini tidak mendukung pengaruh kualifikasi (Ph.D.) dan keahlian SSB terhadap ISR. Temuan ini menyiratkan bahwa DPS perlu meningkatkan frekuensi pertemuan dalam rangka meningkatkan fungsi pengawasan terhadap manajemen bank syariah, termasuk dalam mmendorong pengungkapan ISR yang lebih komprehensif. kontribusi dalam penelitian ini yaitu Penelitian memfokuskan pada karakteristik SSB terhadap ISR dengan menggunakan Syariah Enterprise Theory (SET) untuk memberikan pemahaman yang lebih baik tentang bagaimana faktor-faktor tersebut mempengaruhi pelaksanaan ISR dalam konteks syariah. Kata Kunci: Karakteristik Dewan Pengawas Syariah, Pelaporan Sosial, Bank Syariah, Indonesia. REFERENCES Abdullah, W. A. W., Percy, M., & Stewart, J. (2013). Shari'ah disclosures in Malaysian and Indonesian Islamic banks The Shari'ah governance system. Journal of Islamic Accounting and Business Research, 4(2), 100–131. doi:10.1108/JIABR-10-2012-0063 Adiertanto, C. P., & Chariri, A. (2013). Analisis Pengaruh islamic corporate governance terhadap corporate social responsibility (Studi kasus pada Bank Syariah di Indonesia). Diponegoro Journal of Accounting. Alam, N., Ramachandran, J., & Nahomy, A. H. (2020). The impact of corporate governance and agency effect on earnings management – A test of the dual banking system. Research in International Business and Finance, 54. doi:10.1016/j.ribaf.2020.101242 Almutair, A. R., & Quttainah, M. A. (2017). Corporate governance"¯: Evidence from Islamic banks. Social Responsibility Journal, 13(3), 601-624. doi:10.1108/SRJ-05-2016-0061 Andika, & Aldi. (2020). Indonesia dan Malaysia bisa bergandengan tangan dalam pengembangan Eksyar. Retrived from https://kneks.go.id/ Anisykurlillah, I., Jayanto, P. Y., Mukhibad, H., & Widyastuti, U. (2020). Examining the role of sharia supervisory board attributes in reducing financial statement fraud by Islamic banks. Banks and Bank Systems, 15(3), 106–116. doi:10.21511/bbs.15(3).2020.10 Aracil, E. (2019). Corporate social responsibility of Islamic and conventional banks: The influence of institutions in emerging countries. International Journal of Emerging Markets, 14(4), 582–600. doi:10.1108/IJOEM-12-2017-0533 Aribi, Z. A., Arun, T., & Gao, S. (2019). Accountability in Islamic financial institution: The role of the Shari'ah supervisory board reports. Journal of Islamic Accounting and Business Research, 10(1), 98–114. doi:10.1108/JIABR-10-2015-0049 Baklouti, I. (2020). Is the Sharia supervisory board a friend or an enemy of Islamic banks"¯? Journal of Islamic Marketing, 13(2), 526-541. doi:10.1108/JIMA-04-2020-0118 Basiruddin, R., & Ahmed, H. (2020). Corporate governance and Shariah non-compliant risk in Islamic banks"¯: evidence from Southeast Asia. Corporate Governance, 20(2), 240–262. doi:10.1108/CG-05-2019-0138 Belal, A. R., Cooper, S. M., & Khan, N. A. (2015). Corporate environmental responsibility and accountability: What chance in vulnerable Bangladesh? Critical Perspectives on Accounting, 33, 44–58. doi:10.1016/j.cpa.2015.01.005 Billzha, R. (2018). Pengaruh karakteristik Dewan Pengawas Syariah (DPS) terhadap profitabilitas bank syariah di Indonesia.Scholar Universitas Andalas. Bukair, A. A., & Rahman, A. A. (2015). The Effect of the Board of Directors' Characteristics on Corporate Social Responsibility Disclosure by Islamic Banks. Journal of Management Research, 7(2), 506-519. doi:10.5296/jmr.v7i2.6989 Choudhury, M. A., & Hoque, M. Z. (2006). Corporate governance in Islamic perspective. Corporate Governance, 6(2), 116–128. doi:10.1108/14720700610655132 D'Amato, A., & Gallo, A. (2019). Bank institutional setting and risk-taking"¯: the missing role of directors' education and turnover. Corporate Governance, 19(4), 774–805. doi:10.1108/CG-01-2019-0013 El-Halaby, S., & Hussainey, K. (2016). Determinants of Compliance with AAOIFI Standards by Islamic Banks. International Journal of Islamic and Middle Eastern Finance and Management, 9(1), 143-168. doi:10.1108/IMEFM-06-2015-0074 Farag, H., Mallin, C., & Ow-Yong, K. (2018). Corporate governance in Islamic banks: New insights for dual board structure and agency relationships. Journal of International Financial Markets, Institutions and Money, 54, 59–77. doi:10.1016/j.intfin.2017.08.002 Farook, S., Hassan, M. K., & Lanis, R. (2011). Determinants of corporate social responsibility disclosure"¯: The case of Islamic banks. Journal of Islamic Accounting and Business Research, 2(2), 114–141. doi:10.1108/17590811111170539 Fitria, S., & Hartanti, D. (2010). Islam dan tanggung jawab sosial"¯: studi perbandingan pengungkapan berdasarkan global reporting initiative indeks dan Islamic Social Reporting indeks. Proceeding of Simposium Nasional Akuntansi Universitas Jenderal Soedirman, Purwokerto. Gaganis, C., Lozano-Vivas, A., Papadimitri, P., & Pasiouras, F. (2020). Macroprudential policies, corporate governance and bank risk: Cross-country evidence. Journal of Economic Behavior and Organization, 169, 126–142. doi:10.1016/j.jebo.2019.11.004 Garas, S. N. (2012). The control of the Shari'a Supervisory Board in the Islamic financial institutions. International Journal of Islamic and Middle Eastern Finance and Management, 5(1), 8–24. doi:10.1108/17538391211216794 Garas, S. N., & Pierce, C. (2010). Shari'a supervision of Islamic financial institutions. Journal of Financial Regulation and Compliance, 18(4), 386–407. doi:10.1108/13581981011093695 Gatandi, T. A., & Filianti, D. (2021). Determinan Pengungkapan Islamic Social Reporting Pada Bank Umum Syariah Di Indonesia Tahun 2015-2019. Jurnal Ekonomi Syariah Teori Dan Terapan, 8(6), 727-742. doi:10.20473/vol8iss20216pp727-742 Ghozali, I., & Ratmono, D. (2017). Analisis multivariat dan ekonometrika teori,konsep,dan aplikasi dengan Eviews 10 (2nd ed.). Semarang: Universitas Diponogoro. Grassa, R., Chakroun, R., & Hussainey, K. (2018). Corporate governance and Islamic banks ' products and services disclosure. Accounting Research Journal, 31(1), 75–89. doi:10.1108/ARJ-09-2016-0109 Gustani. (2013). Model pelaporan kinerja sosial perbankan syariah: Implementasi Islamic Social Reporting Indek di Indonesia. JAKIS: Jurnal Akuntansi Dan Keuangan Islam, 2(1), 35-49. doi.org/10.35836/jakis.v2i1.51 Haniffa, R. (2002). Social responsibility disclosure: An Islamic perspective. In Indonesian Management & Accounting Research, 1(2), 128–146. Helfaya, A., Kotb, A., & Hanafi, R. (2016). Qur'anic ethics for environmental responsibility: implications for business practice. Journal of Business Ethics, 150(4), 1105–1128. doi:10.1007/s10551-016-3195-6 Hussain, A., Khan, M., Rehman, A., Sahib Zada, S., Malik, S., Khattak, A., & Khan, H. (2021). Determinants of Islamic social reporting in Islamic banks of Pakistan. International Journal of Law and Management, 63(1), 1–15. doi:10.1108/IJLMA-02-2020-0060 Johnson, S. G., Schnatterly, K., Hill, A. D., & Hill, A. D. (2013). Board composition beyond independence"¯: Social capital, human capital, and demographics. Journal of Management, 39(1), 232–262. doi:10.1177/0149206312463938 Khoirudin, A. (2013). Corporate governance dan pengungkapan Islamic social. Accounting Analysis Journal, 2(2), 227–232. doi:10.15294/aaj.v2i2.2919 Kirana, A. D., & Prasetyo, A. B. (2021). Analyzing board characteristics, ownership structure and company characteristic to CSR disclosure. Accounting Analysis Journal, 10(1), 62–70. doi:10.15294/aaj.v10i1.41944 Koka, S. K., Giorgioni, G., & Farquhar, S. (2022). The trade-off between knowledge accumulation and independence: The case of the Shariah supervisory board within the Shariah governance and firm performance nexus. Research in International Business and Finance, 59(101549). doi:10.1016/j.ribaf.2021.101549 Kusuma, M., & Rosadi, S. (2019). Islamic corporate governance and islamic banking financial performance. Journal of Finance and Islamic Banking, 1(2), 164–179. doi:10.22515/jfib.v1i2.1493 Lestari, P. (2013). Determinants of islamic social reporting in syariah banks"¯: Case of Indonesia. International Journal of Business and Management Invention, 2(10), 28–34. Manaseer, M. F. Al, Al-Hindawi, R. M., Al-Dahiyat, M. A., & Sartawi, I. I. (2012). The impact of corporate governance on the performance of Jordanian Banks. Journal of Scientific Research, 67(3), 349–359. Meiyana, A., & Aisyah, M. N. (2019). Pengaruh kinerja lingkungan, biaya lingkungan, dan ukuran perusahaan terhadap kinerja keuangan dengan corporate social responsibility sebagai variabel intervening. Nominal: Barometer Riset Akuntansi dan Manajemen, 8(1), 1–18. doi:10.21831/nominal.v8i1.24495 Meutia, I., & Febrianti, D. (2017). Islamic social reporting in Islamic banking: Stakeholders theory perspective. Proceeding of The 17th Annual Conference of the Asian Academic Accounting Association, 34(12001), 8. doi: 10.1051/shsconf/20173412001 Mnif, Y., & Tahari, M. (2021). The effect of Islamic banks' specific corporate governance mechanisms on compliance with AAOIFI governance standards. Journal of Islamic Accounting and Business Research, 12(1), 21–43. doi:10.1108/JIABR-11-2018-0188 Muhammad, R., Annuar, H. A., Taufik, M., & Nugraheni, P. (2021). The influence of the SSB's characteristics toward Sharia compliance of Islamic banks. Cogent Business & Management, 8(1). doi:10.1080/23311975.2021.1929033 Mukhibad, H. (2018). Peran Dewan Pengawas Syariah dalam pengungkapan Islamic Sosial Reporting. Jurnal Akuntansi Multiparadigma (JAMAL), 9(2), 299–311. doi:10.18202/jamal.2018.04.9018 Mukhibad, H., & Fitri, A. (2020). Determinant of Islamic Social Reporting (ISR) Disclosure. International Conference on Economics, Business and Economic Education 2019, KnE Social Sciences, 478–489. doi:10.18502/kss.v4i6.6620 Mukhibad, H., Jayanto, P. Y., & Anisykurlillah, I. (2021). Islamic corporate governance and financial statement fraud: a study of Islamic banks. Journal of Governance & Regulation, 10(2), 361–368. doi:10.22495/jgrv10i2siart16 Mukhibad, H., Jayanto, P. Y., Suryarini, T., & Bagas, B. (2022). Corporate governance and Islamic bank accountability based on disclosure-a study on Islamic banks in Indonesia. Cogent Business & Management, 9(1). doi:10.1080/23311975.2022.2080151 Mukhibad, H., Nurkhin, A., Anisykurlillah, I., Fachrurrozie, F., & Jayanto, P. Y. (2023). Open innovation in shariah compliance in Islamic banks - Does shariah supervisory board attributes matter? Journal of Open Innovation: Technology, Market, and Complexity, 9(1), 100014. doi:10.1016/j.joitmc.2023.100014 Mukhibad, H., & Setiawan, D. (2020). Could risk, corporate governance, and corporate ethics enhance social performance"¯? Evidence from Islamic Banks in Indonesia. Indian Journal of Finance, 14(4), 24–38. doi:10.17010/ijf/2020/v14i4/151706 Mukhibad, H., Setiawan, D., Rahmawati, Rochmatullah, M. R., & Warsina. (2022). Accounting-based performance"¯: Evidence from Indonesia. Monetary Economics and Finance, 15(3), 213-231. doi:10.1504/IJMEF.2022.126902 Naheed, R., AlHares, A., & Shahab, Y. (2021). Board's financial expertise and corporate social responsibility disclosure in China. Board's Financial Expertise and Corporate Social Responsibility Disclosure in China, 21(4), 716–736. doi:10.1108/CG-08-2020-0329 Nomran, N. M., Haron, R., & Hassan, R. (2018). Shari'ah supervisory board characteristics effects on Islamic banks' performance: Evidence from Malaysia. International Journal of Bank Marketing, 36(2), 290–304. doi:10.1108/IJBM-12-2016-0197 Nugraheni, P., & Khasanah, E. N. (2019). Implementation of the AAOIFI index on CSR disclosure in Indonesian Islamic banks. Journal of Financial Reporting and Accounting, 17(3), 365–382. doi:10.1108/JFRA-02-2018-0013 OJK. (2020). Laporan perkembangan keuangan syariah Indonesia. Retrieved from https://www.ojk.go.id/id/kanal/syariah/data-dan-statistik/laporan-perkembangan-keuangan-syariah-indonesia/Pages/Laporan-Perkembangan-Keuangan-Syariah-Indonesia-2021.aspx Othman, R., & Thani, A. M. (2010). Islamic social reporting of listed companies In Malaysia. International Business & Economics Research Journal, 9(4), 135–144. doi:10.19030/iber.v9i4.561 Othman, R., Thani, A. M., & Ghani, E. K. (2009). Determinants of Islamic social reporting among top shariah- approved companies in Bursa. Research Journal of International Studies, 12(12), 4–20. Oware, K. M., & Vitor, D. A. (2021). CEO characteristics and environmental disclosure of listed firms in an emerging economy: Does sustainability reporting format matter? Business Strategy and Development, 4(4), 399–410. doi:10.1002/bsd2.166 Pakpahan, Y., & Rajagukguk, L. (2018). Analisis pengaruh profitabilitas, ukuran perusahaan, ukuran dewan komisaris, dan media exposure terhadap pengungkapan tanggung jawab sosial. Jurnal Akuntansi, 18(2), 197–218. Prabowo, M. A., Jamin, M., Saputro, D. J., Mufraini, A., & Agustia, D. (2017). Female executive officers and corporate social responsibility disclosure"¯: Evidence from the banking industry in an emerging market. Journal for Global Business Advancement, 10(6), 631–651. Prastiwi. (2017). Pengaruh karakteristik dewan pengawas syariah terhadap Rasio Non-Performing (NPF) Bank Syariah. Repository Perpustakaan Universitas Gajah Mada. Rahajeng, D. K. (2013). Sharia governance: Sharia supervisory board model of Islamic banking and finance in Indonesia. SSRN Electronic Journal. doi:10.2139/ssrn.2366722 Rahayu, R. sri, & Cahyati, A. D. (2014). Faktor-faktor yang mempengaruhi pengungkapan corporate social responsibility. Jurnal Riset Akuntansi, 3(1), 56–76. doi:10.54964/liabilitas.v3i1.32 Rahman, A., Abdul, & Bukair, A. A. (2013). The Influence of the shariah supervision Board on corporate social responsibility disclosure by Islamic Banks of Gulf Co-Operation Council Countries. Asian Journal of Business and Accounting, 6(2), 65–104. Ramadhani, F. (2016). Pengaruh ukuran perusahaan, profitabilitas, leverage dan ukuran dewan pengawas syariah terhadap pengungkapan Iislamic social reporting (Studi empiris pada bank umum syariah di Indonesia tahun 2010-2014). JOM Fekon, 3(1), 2487–2500. Rashid, M. H. U., Khanam, R., & Ullah, M. H. (2021). Corporate governance and IFSB standard-4: evidence from Islamic banks in Bangladesh. International Journal of Islamic and Middle Eastern Finance and Management, 15(1), 1–17. doi:10.1108/IMEFM-03-2020-0124 Risqi, M. I. M., & Septriarini, D. F. (2021). Determinan Pengungkapan Islamic Social Reporting (ISR) oleh bank syariah di Indonesia dan Malaysia. Jurnal Ekonomi Syariah Teori Dan Terapan, 8(4), 413-425. doi:10.20473/vol8iss20214pp413-425 Rizk, R. R. (2014). Islamic environmental ethics. Journal of Islamic Accounting and Business Research, 5(2), 194–204. doi:10.1108/JIABR-09-2012-0060 Rosiana, R., Arifin, B., & Hamdani, M. (2015). Pengaruh ukuran perusahaan, profitabilitas, leverage, dan Islamic governance score terhadap pengungkapan Islamic social reporting (Studi Empiris pada Bank Umum Syariah di Indonesia tahun 2010-2012). Jurnal Bisnis Dan Manajemen, 5(1), 87–104. doi:10.15408/ess.v5i1.2334  Safiullah, M. (2023). Funding Liquidity in Islamic banks: Does the Shariah supervisory board's higher educational attainment matter? Pacific-Basin Finance Journal, 78. doi:10.1016/j.pacfin.2023.101976 Safiullah, M., & Shamsuddin, A. (2017). Risk in Islamic banking and corporate governance. Pacific-Basin Finance Journal, 47, 129–149. doi:10.1016/j.pacfin.2017.12.008 Sugiono, P. D. (2019). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta CV. Triyuwono, I. (2001). Metafora zakat dan Shari'ah Enterprise Theory sebagai konsep dasar dalam membentuk akuntansi syari'ah. Jurnal Akuntansi dan Auditing Indonesia (JAAI), 5(2), 131–145. Valente, A., & Atkinson, D. (2019). Sustainability in business: A millennials' perspective. Journal of Modern Accounting and Auditing, 15(6), 293–304. doi:10.17265/1548-6583/2019.06.002 Veltrop, D. B., Molleman, E., Reggy, Hooghiemstra, R. B. H., & Ees, H. Van. (2017). Who's the boss at the top? A micro-level analysis of director expertise, status and conformity within boards. Journal of Management Studies, 54(7), 1079–1110. Wang, M., Su, X., Wang, H., & Chen, Y. (2017). Directors' education and corporate liquidity: Evidence from boards in Taiwan. Review of Quantitative Finance and Accounting, 49, 463–485. doi:10.1007/s11156-016-0597-6 Wijayanti, R., & Setiawan, D. (2022). Social reporting by Islamic Banks"¯: The role of sharia supervisory board and the effect on firm performance. Sustainability, 14(7), 1–25. doi:10.3390/su141710965